Minimally invasive approach to low-velocity penetrating extraperitoneal rectal trauma. Issue 1 (12th May 2020) - Melland-Smith, Megan; Chesney, Tyler R; Ashamalla, Shady; Brenneman, Fred
Abstract : Unlike intraperitoneal colorectal injuries, the standard of care for extraperitoneal rectal trauma includes a diverting colostomy due to relative inaccessibility of these injuries for primary repair. New technologies to enhance access to the extraperitoneal rectum have gained increasing use in benign and malignant rectal disease. We present two cases of low-velocity penetrating extraperitoneal rectal trauma. In both cases, a transanal minimally invasive surgery (TAMIS) approach was used to access, and primarily repair, full-thickness rectal lacerations. These patients were successfully managed without a colostomy and without complication. TAMIS enables access to distal rectal injuries, facilitating primary repair and bringing the management of extraperitoneal rectal injuries in line with intraperitoneal injuries, with the potential to avoid fecal diversion.